Description Of Learning Outcomes Through Identifiable Goals - D.I. Yunusova (Zien Journals, 2025)
This article discusses the issues of goal-setting of learning processes, the identification of learning outcomes based on externally expressed, observed and certain mental actions of students
Keywords: learning goal; identification; behaviorism